Using Vlog in the Youtube Channel as a Means To Improve Students’ Motivation And Confidence to Speak English in Intermediate 1 Level of LB-LIA Jambi - Paramita Sari (International Journal of Language Teaching and Education, 2017)
Students find it hard to speak English despite the fact that they have the basic knowledge of the language due to the lack of motivation and confidence. As the technology advances, teachers must be willing to take advantage of the potential channels provided by it. This study aims to improve students’ motivation and confidence to speak English through the use of Vlog in the Youtube Channel as well as to find out the element that affect the most to the improvement of the motivation and confidence. The data were obtained through classroom observations, questionnaires and interviews. In terms of findings, this study revealed that the use of Vlog in the Youtube Channel improved students’ motivation and confidence. The data also suggested that students were most motivated and confident to speak English because they were given enough time to think of what they wanted to talk about and it was done in the place they found familiar. Therefore, teachers are suggested to bring technology into the classrooms more often and adjust it to the situation where students find it convenient to speak up. Keywords: Vlog, Youtube Channel, Motivation, Confidence, English